2019
DOI: 10.3354/dao03369
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tool diagnosis of an outbreak of ranavirosis in amphibian tadpoles in the Canadian boreal forest

Abstract: Investigation of mortalities in isolated wild amphibian populations presents diagnostic difficulties that can hinder reaching a definitive diagnosis for the cause of death. Disease can only be diagnosed when pathogen presence (e.g. detection by PCR) is linked to tissue lesions (histopathology) in the host. We report a 2-site outbreak of ranavirosis in wild anuran tadpoles in the boreal forest of Wood Buffalo National Park, Canada, diagnosed by histologic and molecular techniques. Mortalities occurred in wood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our findings are also consistent with other studies that demonstrated that larval amphibians are more likely to experience lethal RV infections than adults [ (11,12); see also (105) for multi-year data from our study region]. Notably, all positive CT tadpoles were sampled during a single die-off event of the other two species, but did not experience mass-mortality themselves [see (79)]. This could indicate spillover events from WF and/or CF into CT, only occurring when CT are exposed to a large number of infectious particles due to ongoing die-off events in other species.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with other studies that demonstrated that larval amphibians are more likely to experience lethal RV infections than adults [ (11,12); see also (105) for multi-year data from our study region]. Notably, all positive CT tadpoles were sampled during a single die-off event of the other two species, but did not experience mass-mortality themselves [see (79)]. This could indicate spillover events from WF and/or CF into CT, only occurring when CT are exposed to a large number of infectious particles due to ongoing die-off events in other species.…”
Section: Discussionsupporting
confidence: 92%
“…two confirmed die-off events in 2017 at wetlands located 7 and 29 km away from the sampled population (Forzán et al 2019) and mortality occurring among wood frog tadpoles within 3.5 km in 2009 (D.M. Schock, unpublished work).…”
Section: Discussionmentioning
confidence: 61%
“…To investigate ranavirus infection in postmetamorphic amphibians, we exposed terrestrial wood frogs (Rana sylvatica) via bath exposure to environmentally relevant concentrations (Gray et al 2009a) of two isolates of Ranavirus: FV3 wild-type (WT) and the FV3 vIF-2α knockout (KO) as described by Chen et al (2011). We focused our study on wood frogs because FV3-related mortality events in wild anurans in North America are often associated with communities containing this species (e.g., Greer et al 2005;Brunner et al 2011;Forzán et al 2019), suggesting this species to be an important host for FV3. Further, wood frogs have been suggested as a model species for challenge experiments involving North American strains of Ranavirus due to their widespread distribution, sympatry with numerous other amphibian species, and relatively high ranavirus prevalence levels (Lesbarrères et al 2012;Forzán et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All wood frogs used in our study were raised from four egg clutches collected from a natural population within Wood Buffalo National Park which showed low Ranavirus prevalence and low viral loads in 2017 [32]. However, Ranavirus has been commonly observed in amphibians in the area [32,34], with two confirmed die-off events at wetlands 7 and 29 km away in 2017 [28], and mortality occurring among wood frog tadpoles within 3.5 km in 2009 [49]. Additionally, sequencing led to the identification of two different FV3-like viruses in amphibian populations in the research area [33,50].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality events in wild anuran populations in North America are often associated with communities containing wood frogs [e.g. 1,27,28], which could indicate their roles as reservoirs for the pathogen in such communities.…”
Section: Introductionmentioning
confidence: 99%